Analysis of the Role of Agents in Helping Settlement of Insurance Claims at PT. Prudential Life Assurance Binjai Branch - Arini Lestari; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
An Insurance agent is a person chosen by an insurance company who plays a role in finding customers, talk about policy terms, and help policyholders. The purpose of this study is to determine the role of agents insurance in PT. Prudential Life Assurance Cabang Binjai. The method used in this study is a qualitative method with data collection techniques, interview, observation on PT. Prudential Life Assurance Cabang Binjai. The results of this study indicate that agents help participants in resolving claims by explaining the procedure for claims, help complete the documents needed when you want to submit a claim, and waiting for the results of verification and validation until the claim comes out.